Quantifying endothelial cell proliferation in the zebrafish embryo [version 1; peer review: 1 approved, 2 approved with reservations] - Timothy JA Chico; Jovana Serbanovic-Canic; Paul C Evans; George Bowley (F1000Research, 2021)
Introduction: Endothelial cell (EC) proliferation is a fundamental determinant of vascular development and homeostasis, and contributes to cardiovascular disease by increasing vascular permeability to blood-borne lipoproteins. Rodents have been traditionally used to analyse EC proliferation mechanisms in vascular health and disease; however, alternative models such as the zebrafish embryo allow researchers to conduct small scale screening studies in a physiologically relevant vasculature whilst reducing the use of mammals in biomedical research. In vitro models of EC proliferation are valuable but do not fully recapitulate the complexity of the in vivo situation. Several groups have used zebrafish embryos for vascular biology research because they offer the advantages of an in vivo model in terms of complexity but are also genetically manipulable and optically transparent. Methods: Here we investigated whether zebrafish embryos can provide a suitable model for the study of EC proliferation. We explored the use of antibody, DNA labelling, and time-lapse imaging approaches. Results: Antibody and DNA labelling approaches were of limited use in zebrafish due to the low rate of EC proliferation combined with the relatively narrow window of time in which they can label proliferating nuclei. By contrast, time-lapse imaging of fluorescent proteins localised to endothelial nuclei was a sensitive method to quantify EC proliferation in zebrafish embryos. Discussion: We conclude that time-lapse imaging is suitable for analysis of endothelial cell proliferation in zebrafish, and that this method is capable of capturing more instances of EC proliferation than immunostaining or cell labelling alternatives. This approach is relevant to anyone studying endothelial cell proliferation for screening genes or small molecules involved in EC proliferation. It offers greater biological relevance than existing in vitro models such as HUVECs culture, whilst reducing the overall number of animals used for this type of research.